How Defendant Characteristics Affect Sentencing and Conviction in the US - Kuenzli, Payton (2018)
This research study analyzes whether or not there is any relationship between sentencing and conviction and certain defendant characteristics in the US legal system. In the midst of a time where the nation is strongly divided politically, the topic is often the center of research projects and discussions in academic journals. Specifically, this research explores the 3 characteristics- race, gender, and socioeconomic status. Within this article, multiple case studies from other journals are cited in which research and experiments have suggested that these factors do have influence on both whether or not a defendant gets convicted or for how long the defendant is sentenced. With these cases in mind, we try to test the theory for ourselves in a survey experiment amongst college students. The survey tests cases with instances of academic dishonesty in university with the defendant characteristics being manipulated for race, gender, and socioeconomic status. However, the results were inconclusive of any sort of link between those characteristics and the sentencing in the study